2019
DOI: 10.1126/sciadv.aaw0341
|View full text |Cite
|
Sign up to set email alerts
|

Extreme events reveal an alimentary limit on sustained maximal human energy expenditure

Abstract: The limits on maximum sustained energy expenditure are unclear but are of interest because they constrain reproduction, thermoregulation, and physical activity. Here, we show that sustained expenditure in humans, measured as maximum sustained metabolic scope (SusMS), is a function of event duration. We compiled measurements of total energy expenditure (TEE) and basal metabolic rate (BMR) from human endurance events and added new data from adults running ~250 km/week for 20 weeks in a transcontinental race. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 45 publications
3
117
0
1
Order By: Relevance
“…Consistent with these reports, recent analysis of energy expenditure during pregnancy (Dunsworth, Warrener, Deacon, Ellison, & Pontzer, ) and by athletes participating in contests ranging from half‐day triathlons to multimonth ultra‐endurance runs revealed an ultimate limit of sustainable energy expenditure (Thurber et al, ). Thurber and colleagues found that over time the maximal daily energy output decreases curvilinearly to a value below three times basal metabolic rate.…”
Section: Evolved Constraints Of Energy Expenditurementioning
confidence: 59%
“…Consistent with these reports, recent analysis of energy expenditure during pregnancy (Dunsworth, Warrener, Deacon, Ellison, & Pontzer, ) and by athletes participating in contests ranging from half‐day triathlons to multimonth ultra‐endurance runs revealed an ultimate limit of sustainable energy expenditure (Thurber et al, ). Thurber and colleagues found that over time the maximal daily energy output decreases curvilinearly to a value below three times basal metabolic rate.…”
Section: Evolved Constraints Of Energy Expenditurementioning
confidence: 59%
“…Human endosomatic needs due to nourishment have been estimated in c. 10 (MJ edible /(p•d)), but recent studies suggest they can reach up to 25 [13], which roughly corresponds to an interval 0.087-0.217 (toe/(p•y)) and depends on individual physical activities and metabolism. In this respect, Sanfilippo et al [14] studied the energy requirements and the environmental impact of different dietary choices and concluded that beef-based meals present a cumulative energy demand (CED) footprint which is 6.25 times the edible energy in foods, while the vegetarian menu merely requires 3.28 and the poultry and pork choices demand intermediate values between 3.50-4.50.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental models that test the limits of human function have been instrumental in characterising the capacity and regulation of numerous physiological systems, including the capacity for maximal O 2 uptake (1) , time spent without energy intake (2) and most recently maximal levels of sustained energy expenditure (3) . This approach advances our fundamental understanding of human physiology and provides important insights into susceptibility towards pathophysiology.…”
mentioning
confidence: 99%